O uso dos recursos tecnológicos no ensino de geografia nas turmas de 6º ao 9º ano do ensino fundamental na E.M.E.F. Nova Vida - Assurini - Altamira-PA - MENEZES, Jéssica Cruz de (2022)
We live in the age of technology, technological resources is something present in the everyday of the student. Education can not be treated as something isolated from the knowledge society, information networks are present in the school space. Thus, it is necessary to think about new pedagogical didactics that accompany this new tendency to interdisciplinary, teaching based on the interdependence between the different areas of knowledge, that is, to explore the possibilities that technology offers to the process of teaching learning. In this way, the school plays the predominant role in the formation of individuals able to use such technologies, fulfilling its role of training citizens to understand the world in which they live. The present research aims to analyze how the use of technological resources can favor the learning process of teaching geography in the elementary school classes from the 6th to the 9th year in the Nova Vida municipal school, rural area of the municipality of Altamira-PA. How they are used by educators to make geography classes dynamic and motivating together with the importance of these resources in the learning teaching process. Which shows positive results and great acceptance in the classroom, both by the students and the teacher. Using the following methodological procedures; bibliographical research, direct observation of pedagogical practice in E.M.E.F: Nova Vida.